Breaking Barriers: The Detrimental Effects of Combined Ragweed and House Dust Mite Allergen Extract Exposure on the Bronchial Epithelium - Răzvan-Ionuț Zimbru; Manuela Grijincu; Gabriela Tănasie; Elena-Larisa Zimbru; Florina-Maria Bojin; Roxana-Maria Buzan; Tudor-Paul Tamaș; Monica-Daniela Cotarcă; Octavia Oana Harich; Raul Pătrașcu; Laura Haidar; Elena Ciurariu; et al. (Applied Sciences)
(1) Background: Respiratory allergens, particularly ragweed (RW) pollen and house dust mites (HDMs), are major triggers of respiratory inflammation and allergic diseases. This study investigated the impact of single- versus combined-allergen exposure on the barrier function of normal human bronchial epithelial (NHBE) cells cultured at the air–liquid interface (ALI). (2) Methods: NHBE cells were exposed to RW pollen extract (200 µg/mL), HDM extract (200 µg/mL) and their combination at varying concentrations (200 µg/mL, 100 µg/mL, 50 µg/mL, 25 µg/mL). Additional groups included a mixture of Amb a 1, Amb a 11 and Amb a 12 (100 mg/mL) and combinations of Der p 1 with the ragweed allergens (50 mg/mL, 100 µg/mL). Transepithelial electrical resistance (TEER) was recorded over 72 hours to assess barrier integrity, and immunofluorescence (IF) staining for zonula occludens-1 (ZO-1) was performed to evaluate tight junction alterations. (3) Results: TEER measurements showed a significant reduction in epithelial barrier integrity following allergen exposure, with the most pronounced disruption observed with the combined exposure to RW and HDM groups. IF staining confirmed extensive tight junction damage, highlighting their synergistic impact. (4) Conclusions: These findings emphasize the importance of assessing cumulative allergen effects, as combined exposure may exacerbate epithelial dysfunction and represent a key aspect in the management of allergic rhinitis and asthma.